Smart Computing Techniques and Applications Proceedings of the Fourth International Conference on Smart Computing and Informatics, Volume 2 - Satapathy, Suresh Chandra; Bhateja, Vikrant; Favorskaya, Margarita N.; Adilakshmi, T. (Smart Innovation, Systems and Technologies, 2021)
XXII, 827 p. 432 illus., 308 illus. in color.